Change in footstrike position is related to alterations in running economy in triathletes - Bonacci, J.; Green, D.; Saunders, P.; Blanch, P.; Franettovich, M.; Chapman, A.; Vicenzino, B. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Biomechanical factors are likely related to the impairment in running economy frequently observed in triathletes when running after cycling (Millet et al., 2000). Cycling has been shown to interfere with muscle recruitment during subsequent running in some highly-trained triathletes (Chapman et al., 2008), but the implications of this on run performance are unknown. Links between muscle recruitment and running economy have been established during isolated running (Paavolainen et al., 1999), which compel the proposition that any change in muscle recruitment following cycling might be associated with running economy. Stride frequency, stride length and hip and knee angles have been reported to be unchanged after cycling (Quigley & Richards, 1996; Hue et al., 1997), however, muscle recruitment and limb movement have not been simultaneously measured in previous studies that have investigated the relationship between biomechanical factors and running economy after cycling. The purpose of the current investigation was to evaluate changes in neuromuscular control (muscle and movement control) during running after a 45 min high-intensity cycle and their relationships to alterations in running economy.